Critical success factors of knowledge on sustainability in Malaysian higher education - Abdul Karim, Aini Arifah; Abdullah, Sabrina J. Ho; Mohd Ayub, Ahmad Fauzi; Sharaai, Amir Hamzah (Science Research Society, 2021)
This study aims to investigate Malaysia’s Institutes of Teacher Education (ITE) students’ knowledge on sustainability toward environmentally sustainable behaviour (ESB).The model adapted is based on Hines, Hungerford and Tomera’s Environmental Responsible Behaviour Model which was established since 1987.The nature of this study was descriptive, and the data were collected using cross-sectional survey. A total of 425 participants responded to a questionnaire developed for this study. Several procedure was carried out in order to assess the validity and reliability of the questionnaire using PLS-SEM. The study revealed that the Malaysian Higher Education students showed a high level of knowledge of sustainability action skills, knowledge of sustainability strategies and knowledge of sustainability issues toward ESB and the environment. Findings associated with students’ gender, age, ethnicity, field of study and academic program were also reported and discussed. First, the participating students came from Institutions of Teacher Education. Although this institution is a major teacher training centre in the nation, further studies should include samples from other public and private institutions. Second, this study did not examine the correlation among the three main components: knowledge of sustainability action skills, knowledge of sustainability strategies and knowledge of sustainability issues. Limited studies have been conducted in Malaysia on ITE although the institutions are supporting ESD through the Sustainable ITE program. Therefore, this study is exploring the critical success factors of knowledge on sustainability action skills, knowledge on sustainability strategies and knowledge on sustainability issues on environmentally sustainable behaviour of teacher candidate students in Malaysia. In addition, past studies have recommended to investigate and look into the environmentally sustainable behaviour among the younger generations, especially those with higher education levels, especially because inevitably, they are agents of change, and also they will be affected by the environmental issues that are caused by the current human activities.